Armed to Kill: A Cross-Sectional Analysis Examining the Links between Firearms Availability, Gun Control, and Terrorism Using the Global Terrorism Database and the Small Arms Survey - Bureš, Oldrich (Terrorism and political violence, 2025)
According to the Global Terrorism Database, the use of firearms in terrorist attacks has been on the rise, and firearms-based attacks are the most lethal. In the aftermath of mass-casualty attacks perpetrated with firearms, policymakers across the world advocate tightened gun control to restrict terrorists’ access to both licit and illicit guns. However, academic research on the linkages between firearms availability, gun control legislation, and terrorism is scarce. This study fills this research gap by conducting a systematic cross-sectional analysis of the linkage between gun control, licit and illicit stocks of firearms, and terrorist attacks in 2015–2019, based on a novel dataset incorporating the Global Terrorism Database and the Small Arms Survey. Our estimation using OLS regression shows a strong relationship between the availability of firearms and the incidence of gun-based terrorism, especially for lone wolf attacks. Furthermore, terrorists in stable, democratic countries are comparatively more likely to select firearms as their weapon of choice. Conversely, strict gun control only slightly alleviates the overall risk of terrorism in stable countries but does not impact weapon selection. In unstable countries in the grip of intrastate conflict, gun control significantly reduces lone wolf-style attacks, while organized multi-perpetrator attacks are not deterred.